The Predictive Value of ACR TI-RADS Classification for Central Lymph Node Metastasis of Papillary Thyroid Carcinoma: A Retrospective Study. (7th February 2022) - Zhong, Minying; Zhang, Zhaoming; Xiao, Yisheng; He, Yanping; Chen, Yongyu; Huang, WeiJun; Lu, Liping
Abstract : Background . The aim of this retrospective study was to evaluate the risk factors for central lymph node metastasis (CLNM) in papillary thyroid carcinoma (PTC), according to the guidelines of the 2017 Thyroid Imaging Report and Data System (TI-RADS) published by the American College of Radiology (ACR). Methods . This study included a retrospective analysis of 844 patients with PTC who were pathologically diagnosed, treated with central lymph node dissection, and divided into CLNM and nonmetastatic groups. Univariate and multivariate analyses were performed to determine the relationship between the TI-RADS score and CLNM. Results . Among 844 patients, 439 developed CLNM, with a metastasis rate of 52% and a TI-RADS score of 9.42 ± 2.262, which were higher than those of the non-CLNM group (P < 0.05 ). Univariate analysis demonstrated that the sex, location, maximum diameter of the nodule, multifocality, margin, shape, calcification, and TI-RADS score were related to CLNM (P < 0.05 for all). However, multivariate logistic regression analysis demonstrated that female, maximum diameter of the nodule, multifocality, a taller-than-wide shape, and high TI-RADS score were the independent risk factors for CLNM (P < 0.05 for all). Conclusion . The TI-RADS score combined with sex, nodule size, shape, and multifocality has a certain predictive effect on CLNM, which can provide a reference to the clinicians for further treatment strategies.